Legal Accountability in the Delegation of Authority from Obstetricians to Midwives in Maternal and Child Hospitals - Desak Gede Dhyanada Kirana Nurharta; Ida Bagus Surya Dharmajaya; Ida Bagus Gede Fajar Manuaba (GLOBAL HEALTH SCIENCE GROUP, 2025)
According to Law No. 4 of 2019 concerning Midwifery, midwives are recognized as part of the health workforce, alongside physicians, who are authorized to provide medical services. In practice, midwives interact directly with both patients and other healthcare professionals during service delivery. In many instances, a delegation of authority from physicians, especially specialists, to midwives is necessary to ensure effective inter-professional collaboration. This study aims to know about legal accountability in the delegation of authority from obstetricians to midwives in maternal and child hospitals. The research employed a literature review design using a comprehensive strategy. Articles were sourced from international research journal databases accessed via the internet, specifically ScienceDirect, PubMed, and Google Scholar. All searches were conducted in May-June 2025, focusing on articles published between 2016 and 2024. The keywords used in this literature review were adapted from the Medical Subject Heading (MeSH) terms, including